Cyclin D1b induces changes in the macrophage phenotype resulting in promotion of tumor metastasis. Issue 24 (December 2021) - Wang, Yuxue; Liu, Yi; Xiang, Lei; Han, Lintao; Yao, Xiaowei; Hu, Yibing; Wu, Fenghua
In breast cancer, tumor-associated macrophages with activated phenotypes promote tumor invasion and metastasis. The more aggressive mesenchymal-like breast cancer cells have a selective advantage, skewing macrophages toward the more immunosuppressive subtype. However, the mechanism underlying this shift is poorly understood. Cyclin D1b is a highly oncogenic variant of cyclin D1. Our previous study showed that non-metastatic epithelial-like breast cancer cells were highly metastatic in vivo when cyclin D1b was overexpressed. The present study determined whether cyclin D1b contributed to the interaction between breast cancer cells and macrophages. The results showed that cyclin D1b promoted the invasion of breast cancer cells in vitro . Specifically, through overexpression of cyclin D1b, breast cancer cells regulated the differentiation of macrophages into a more immunosuppressive M2 phenotype. Notably, tumor cells overexpressing cyclin D1b activated macrophages and induced migration of breast cancer cells. Further investigations indicated that SDF-1 mediated macrophage activation through breast cancer cells overexpressing cyclin D1b. These results revealed a previously unknown link between aggressive breast cancer cells and Tumor-associated macrophages, and highlighted the importance of cyclin D1b activity in the breast cancer microenvironment.